Cyclosporine A impairs bone repair in critical defects filled with different osteoconductive bone substitutes - Fernanda Castanheira GONÇALVES; Guilherme José Pimentel Lopes de OLIVEIRA; Cassio Rocha SCARDUELI; Rubens SPIN-NETO; Andreas STAVROPOULOS; Rosemary Adriana Chiérici MARCANTONIO (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of this study was to assess the influence of cyclosporine administration on the repair of critical-sized calvaria defects (CSDs) in rat calvaria filled with diverse biomaterials. Sixty animals were divided into two groups: the control (CTR) group (saline solution) and the cyclosporine (CCP) group (cyclosporine, 10 mg/kg/day). These medications were administered daily by gavage, beginning 15 days before the surgical procedure and lasting until the day the animals were euthanized. A CSD (5 mm Ø) was made in the calvaria of each animal, which was allocated to one of 3 subgroups, according to the biomaterial used to fill the defect: coagulum (COA), deproteinized bovine bone (DBB), or biphasic calcium phosphate ceramics of hydroxyapatite and β-phosphate tricalcium (HA/TCP). Euthanasia of the animals was performed 15 and 60 days after the surgical procedure (n = 5 animals/period/subgroup). Bone repair (formation) assessment was performed through microtomography and histometry, while the analyses of the expression of the BMP2, Osteocalcin, and TGFβ1 proteins were performed using immunohistochemistry. The CSDs not filled with biomaterials demonstrated lower bone formation in the CCP group. At 15 days, less bone formation was observed in the CSDs filled with DBB, a smaller volume of mineralized tissue was observed in the CSDs filled with HA/TCP, and the expression levels of BMP2 and osteocalcin were lower in the CCP group compared to the CTR group. The use of cyclosporine impaired bone repair in CSD, and this effect can be partially explained by the suppression of BMP2 and osteocalcin expression.